Risk-adjusted return: banking sector analysis through the RAROC model - Schuster, Wagner Eduardo (2020)
Bank sector scenario in Brazil nowadays is facing increasingly competitiveness and credit loans expansion. Moreover, the resources are scarce and the decision to allocate capital to a product or another represents an important trade-off for managers, what reinforces using robust decision-making tools that consider risk to maximize returns. The aim of this work was to analyze the risk-adjusted return for the banking sector through the RAROC model based on three perspectives: Regulatory, Economic and Forecasted RAROC. The database was provided by a financial institution and contains data for the two core business products (Payroll-linked and Working Capital loans) as well as macroeconomic variables. This work contributes to the literature by proposing a new approach which enables to measure profitability stratified within the institution's portfolio and furthermore to project its values. Methodologically, a Value at Risk (VaR) model with Monte Carlo Simulations was used for the Economic RAROC, a Vector Autoregressive (VAR) model for Forecasting and a historical approach for the Regulatory RAROC. Through Regulatory RAROC an ex-post analysis, month by month, reveals that the Payroll-linked loans returned 8.13% on average with positive and superior average market values throughout the entire period, while Working Capital presented 4.03%, but a result that varied greatly with several negative returns. Furthermore, the Economic Capital calculated for Payroll-linked was substantially lower than the Regulatory while in Working Capital was the contrary, reinforcing that the first would present a much higher return as optimizing the allocated capital (from 6.87% to 45.75% in 2019M06), highlighting the relevance of an internal model. Finally, the Forecasting RAROC enables an ex-ante prospective decision and the results reveals that in a 12-month future scenario the Payroll-linked would return 9.31% in average while Working Capital would present 1.29%, confirming that the first product will continue to remunerate the invested capital properly while the second has a potential for return, however without measures that change the current projected scenario, the product does not present itself as a good capital investment. To conclude, the overall tests reveal that the models had a good performance and therefore bring innovative results that satisfactory contributes to a strategic management focused on risks.